Materials Pushing the Application Limits of Wire Grid Polarizers further into the Deep Ultraviolet Spectral Range. Issue 11 (14th July 2016) - Siefke, Thomas; Kroker, Stefanie; Pfeiffer, Kristin; Puffky, Oliver; Dietrich, Kay; Franta, Daniel; Ohlídal, Ivan; Szeghalmi, Adriana; Kley, Ernst‐Bernhard; Tünnermann, Andreas
Abstract : Wire grid polarizers (WGPs), periodic nano‐optical metasurfaces, are convenient polarizing elements for many optical applications. However, they are still inadequate in the deep ultraviolet spectral range. It is shown that to achieve high performance ultraviolet WGPs a material with large absolute value of the complex permittivity and extinction coefficient at the wavelength of interest has to be utilized. This requirement is compared to refractive index models considering intraband and interband absorption processes. It is elucidated why the extinction ratio of metallic WGPs intrinsically humble in the deep ultraviolet, whereas wide bandgap semiconductors are superior material candidates in this spectral range. To demonstrate this, the design, fabrication, and optical characterization of a titanium dioxide WGP are presented. At a wavelength of 193 nm an unprecedented extinction ratio of 384 and a transmittance of 10% is achieved. Abstract : The application ranges of several materials for the realization of nano‐optical wire grid polarizers (WGPs) are discussed. The study shows that high performance WGPs require materials with large absolute values of their complex permittivities and extinction coefficients. Based on these results a titanium dioxide WGP was fabricated with an unprecedented extinction ratio of 384 at a wavelength of 193 nm.